Design of an Aperture-Coupled Patch Antenna for Unmanned Aerial Vehicle Communication - P., Nikkila Paul; T., Anita Jones Mary Pushpa (Journal of Trends in Computer Science and Smart Technology, 2025)
The aperture-coupled patch antenna, characterized by its low profile and cost-effectiveness, has been developed for Unmanned Aerial Vehicle (UAV) communication in this research. A significant advantage of the aperture-coupled patch antenna is its simplified design process compared to other antenna types. This configuration minimizes complexity of transmission lines while enhancing the radiation pattern and plane. In the context of UAV communication, the aperture-coupled patch antenna is crucial, faciliating efficient communication between users. It effectively transmits electromagnetic energy and minimizes interference, thereby improving communication efficiency in UAV applications. The performance of the designed aperture-coupled patch antenna has been evaluated through simulation results, demonstrating high gain, an optimal radiation pattern, a low Voltage Standing Wave Ratio (VSWR), and a strong polarization ratio.
Keywords: Aperture-Coupled Patch Antenna; Patch Antenna; Unmanned Aerial Vehicles Communication; High Efficiency; Antenna Gain